2012
DOI: 10.5398/medpet.2012.35.3.179
|View full text |Cite
|
Sign up to set email alerts
|

Fiber Quality of Iranian Carpet-Wool Sheep Breeds

Abstract: ; 84,2%±0,6%; 9,8%±0,4%; 5,9%±0,4%; dan 69,3%±0,7%. MFD 22% dari seluruh sampel wol adalah 22-30 µm. MFD 36% dari sampel wol adalah antara 31-37 µm dan 42% lebih dari 37 µm. SL dari 12% sampel wol lebih pendek dari 100 mm, 38% sampel antara 100-120 mm, dan 50% sampel lebih panjang dari 120 mm. Karakteristik tersebut merupakan lingkup penting untuk meningkatkan kualitas serat yang dihasilkan bangsa-bangsa domba Iran melalui seleksi genetik.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…These wool yields are comparable with the wool yields reported previously. For instance, Harizi et al [21] reported wool yields ranging from 50-70% for a Tunisian sheep breed, likewise, Ansari-Renani et al [22] also reported 69.3 ± 0.7% at most for the Iranian sheep breeds. Larger wool yields gain the attention of worldwide wool textile industries, and thus help a country to boost its economy.…”
Section: Wool Yield (Y)mentioning
confidence: 99%
“…These wool yields are comparable with the wool yields reported previously. For instance, Harizi et al [21] reported wool yields ranging from 50-70% for a Tunisian sheep breed, likewise, Ansari-Renani et al [22] also reported 69.3 ± 0.7% at most for the Iranian sheep breeds. Larger wool yields gain the attention of worldwide wool textile industries, and thus help a country to boost its economy.…”
Section: Wool Yield (Y)mentioning
confidence: 99%
“…Carpet wool quality and its value are primarily determined by fiber diameter and length which reflect fineness and the degree of wool growth respectively. 8 Similarly, research results indicated that the wool fibers exposure to UV irradiation resulted in better shrinkage and dye ability. Enzyme treated fibers resulted in better dye rate and improved resistance to shrinkage (Wang et al 2020).…”
Section: Introductionmentioning
confidence: 96%
“…The most important determinants of animal fibre quality are the species that produce it and the diameter of the fibre, as previously described for Iranian cashmere (AnsariRenani et al 2011a, b;Ansari-Renani 2012). The fleece of cashmere goats are double coated and consist of two major fibre types: coarse, medullated guard hair and fine, nonmedullated insulative down fibre (Allain 1992;Mitchell et al 1991;Nixon et al 1991;Ryder 1966;Carter and Clark 1943;Petrie 1995).…”
Section: Introductionmentioning
confidence: 97%